The system of activities for learning English speech etiquette for 8-9 grade Karakalpak students - Khurmetullaevna, Uteshova Zernegul (The journal of contemporary issues in business and government, 2021)
This article analyzes the modern development of teaching speech etiquette (SE) and describes the importance of using activities to improve speech competence of 8-9 grade students in Karakalpakstan. In the present work the author develops a system of activities and exercises consisting of a complex or series of exercises aimed at mastering the linguoculturological features of the speech etiquette (SE) within the framework of a culture of communicative behaviour. Currently the rate of development is increasing in the world, thus, acquiring foreign languages is becoming vitally important for the development of our society. In our country, primary and secondary schools have started using state-of- the-art methods in teaching the English as a foreign language in Karakalpak classrooms. However, there is still necessity of improving language and speech competence as well as the culture of communication.